Transvaginal ultrasound for cervical assessment versus digital vaginal examination during active phase of labour - Hefila, Nermeen Mohamed; Elfazari, Hisham Adel (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Ultrasound is found to have many uses in obstetrics. As the transvaginal ultrasound is used to examine the cervix in non-pregnant cases, it’s also can be used in pregnant cases to detect any cervical changes early in pregnancy, in cases of cervical incompetence, or late in pregnancy in labour to detect progression of cervical changes. Vaginal birth occasionally requires urgent medical intervention to avoid harm to the labouring woman and her baby. Intrapartum ultrasound is a simple technique that improves the understanding of abnormal labour and provides a more scientific basis for assessing labour. In this study, two hundred pregnant women, full term, non-complicated, single tone, cephalic presentation, active stage of labour, attending El-Shatby Maternity University Hospital labour ward were recruited for this study. Methods: Intrapartum transvaginal ultrasound is done by the obstetrician followed immediately by digital examination done by a second obstetrician in charge to avoid bias. Results: The results revealed that comparison between mean cervical length measurements assessed by TVUS and digitally revealed statistically significant difference with p<0.001. Also, comparison between mean cervical diameter measurements assessed by TVUS and digitally reveals statistically significant difference with p<0.001. Conclusions: The TVUS is a suitable alternative to digital examiation in assessing labour progress because it is well accepted, minimal-invasive, less painful and with minimal infectious risks and good tool for estimating labour progress.